A Short Commentary on Potential Role of the IFN-γ/mini-TrpRS Signaling Axis in Abdominal Aortic Aneurysm - Moran, Corey S; Velu, Ramesh B; Vangaveti, Venkat; Malabu, Usman H; Biros, Erik (Archives of Clinical and Biomedical Research, 2020)
Aneurysms demonstrate vascular smooth muscle cells (VSMC) phenotypic modulation characterized by the prevailing of synthetic over contractile properties. We have shown previously the ability of interferon-gamma (IFN-γ) to switch VSMC from contractile to synthetic phenotype via upregulating the truncated form of tryptophanyl-tRNA synthetase (mini-TrpRS) in vitro. Here we discuss a possible role of the IFN-γ/mini-TrpRS signalling axis in the pathology of human abdominal aortic aneurysm (AAA).